Genômica e caracterização fenotípica de bacteriófagos para biocontrole de salmonella enterica - Pottker, Emanuele Serro (2016)
Salmonella spp. it is one of the main pathogens involved in disease outbreaks foodborne (DTA). It is one of the pathogens most prevalent in poultry products in several countries, with world and highlighted important public health distribution. However, bacterial resistance to antimicrobials is a risk to human and animal health due to therapeutic difficulties and the possibility of horizontal transmission of resistance genes between different bacteria. Thus, it emphasizes the need for new tools for treatment against these pathogens. Among them, there is the biological control with the use of bacteriophages, which are bacterial viruses, intracellular binding, host-specific, infecting only prokaryotes. The use of bacteriophage is an alternative to antibiotic therapy, in addition to prevention, it can also be considered supplementary to the use of conventional therapies. Thus, in Chapter 1 we tested the bacterial susceptibility to bacteriophage P22 to different serotypes of Salmonella enterica. We found that the P22 phage lytic action had to infect different strains of Salmonella. In Chapter 2, we selected 12 serotypes of Salmonella enterica (S. Anatum, S. Agona, S. Brandenburg, S. Bredeney, S. Infantis, S. Lexington, S. Panama, S. Rissen, S. Schwarzengrund, S. Tennessee S.Enteritidis ATCC 13076 and S. Typhimurium ATCC 14028) as host bacteria for the isolation and phenotypic characterization of bacteriophage lytic action opposite to these bacteria. It was isolated, characterized and sequenced a new bacteriophage, not yet described, calledSalmonella phage UPF_BP1, which has the circular genome, double-stranded DNA, 39,902 bp., Caudovirales belongs to the order and Podoviridae family. None of the hypothetical Salmonella phage UPF_BP1 proteins showed significant similarity with known or factors involved in bacterial pathogenicity. The new phage lytic action confirmed front of the strains tested, proving to be able to use it in future applications in biocontrol and phage therapy of Salmonella enterica. However it is noteworthy that also isolate another bacteriophage, named 5: 2, which is in genetic sequencing phase.